Uma proposta de sequência didática para o ensino de matrizes no Ensino Médio - Trindade, Jane Rodrigues (2017)
This work has as main objective to develop the mathematical practice presenting the matrix subject in such a way that the student develops the mathematical knowledge and is able to answer that pragmatic question: "why one learns this?" It is known that the presented theme does not have an approach prior to the second year of high school, with the intuitive notion of matrices seen superficially in the analysis and construction of tables. This fact generates great difficulty of understanding by the students, who cannot relate the study to practical situations. Our goal here will be to realize the theory through everyday problems- situations. To do so, we organized the work in a didactic sequence distributed in classes followed by four practical applications, about graphs, coding, gaussian elimination and matrix product.